2023
DOI: 10.3390/life13051122
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin A on Immune Responses and Vitamin A Metabolism in Broiler Chickens Challenged with Necrotic Enteritis

Abstract: Necrotic enteritis (NE) is an important enteric inflammatory disease of poultry, and the effects of vitamin A (VitA) on NE birds are largely unknown. The present study was conducted to investigate the effects of VitA on the immune responses and VitA metabolism of NE broilers as well as the underlying mechanisms. Using a 2 × 2 factorial arrangement, 336 1-day-old Ross 308 broiler chicks were randomly assigned to 4 groups with 7 replicates. Broilers in the control (Ctrl) group were fed a basal diet without extra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Indeed, there is a correlation between serum total protein, albumin, globulin, and the antibody response indicative of immunity in broiler chicks ( 35 , 36 ). Antibody titers serve as indicators of antibody levels in the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is a correlation between serum total protein, albumin, globulin, and the antibody response indicative of immunity in broiler chicks ( 35 , 36 ). Antibody titers serve as indicators of antibody levels in the bloodstream.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Zhang et al [95] reported that vitamin A supplementation improved immune function against infectious disease, inhibited viral infection, and suppressed excessive inflammation process. Moreover, Guo et al [96] concluded that vitamin A supplementation in the diet improved the immune response in necrotic enteritis-challenged birds. It was reported that vitamin A increased antibody responses to T-cell-dependent antigens [97].…”
Section: Immunitymentioning
confidence: 99%
“…Retinol acetate (RA), a vital derivative of vitamin A, undergoes metabolic conversion to active vitamin A, playing a critical role in numerous physiological functions . Its benefits include protecting epithelial cells from radiation damage, , preventing skin aging, and inhibiting acne formation . RA has demonstrated superior efficacy compared to those of other vitamin A derivatives.…”
Section: Introductionmentioning
confidence: 99%